METODE FULL TIME EQUIVALENT UNTUK PENGUKURAN BEBAN KERJA MEKANIK DIVISI WORKSHOP DI PABRIK KERNEL OIL - Alfi, Rizki; Azzahra, Aziza; Arsil, Fikri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2024)
Activities in carrying out work often make workers feel tired, especially work that requires continuity, skill and concentration. Work activities like this can be quite burdensome for mechanics, which can cause fatigue or injury to workers. On the other hand, a workload that is too light can cause workers to become bored or bored with their work. The aim of this research is to determine the workload in each division area studied, and to estimate the right number of workers for a particular position so that it can be a recommendation for companies regarding workload. The Full Time Equivalent (FTE) method is a method for measuring workload by measuring the length of time needed to complete a given task. After carrying out the calculations, the FTE index values are obtained as follows; 1) The press station mechanic is in the 4.39 category (overload), indicating that 2 more employees are needed. 2) General installation mechanics of 0.34 category (underload). This indicates that there is no need for additional employees, but perhaps a reduction in employees to 1 person. 3) Workshop mechanics amounted to 3.63 in the category (overload). This indicates that 2 more mechanics are needed. 4) Mechanical electrical installation is 0.45. This indicates that there is no need for additional mechanics in this area. By calculating the FTE method, it can be seen that there are 2 divisions that fall into the overload workload category, and 2 divisions that fall into the underload workload category. The results of this research are quantitative and from a macro perspective, so it is necessary to also consider socio-cultural factors with employment regulations.